MENINGKATKAN KEMAMPUAN PENGOPERASIAN PERKALIAN MELALUI METODE HORIZONTAL BAGI ANAK TUNARUNGU - Rahmi - Halfi (Jurnal Penelitian Pendidikan Khusus, 2012)
The research was carried out on a child in sixth grade Deaf X SLB N 2 Padang, from observations found the child in completing multiplication problems using inserts do not understand. Thus the researchers want to improve the operation of multiplication through horizontal method. Type of research is to design Researct Sunject Single A - B. Target size by the percentage of their behavior, the child was told to solve the problems multiply, and researchers recorded the results and calculated using percentages.